RESEARCH ON AXIAL LOAD CARRYING CAPACITY OF A NEW TYPE OF SUPERCELL HONEYCOMB STRUCTURE - HE Bin; LI Xiang (Jixie qiangdu)
Axial load carrying capacity is one of the most important mechanical property indexes of honeycomb structure. A new type of supercell honeycomb structure was put forward in which rhombus and circle were combined into the basic cell,and research was focused on its structural stability,overall strength and stiffness. By helps of finite element numerical simulation,the method of eigenvalue buckling analysis was used to realize the process of structural stability analysis of the supercell honeycomb,and the analysis result was also compared with those of rhombus,regular hexagon and regular octagon honeycomb structure.Meanwhile,a type of chassis deck of electrical motorcycle was taken as an example to testify the overall strength and stiffness of the new type of honeycomb sandwich structure’s core under axial load and analyze the influence on strength and stiffness of the core with different wall thickness of its cell. The results show that the new type of supercell honeycomb is an innovative configuration with good comprehensive mechanical properties such as better axial structural stability,high strength and overall stiffness of honeycomb sandwich structure’s core,and axial load-bearing capacity.